Secondary technical school for leading workers in the Polish vocational education system (1971-1982) - Eleonora Sapia-Drewniak (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
In 1971, upon the initiative of the United Polish Workers' Party - the ruling force in the period of the Polish People's Republic - there was established secondary technical school designed for leading workers. The Resolution No. 124 of the Council of Ministers of 1 July 1971 opened the possibility for workers to gain vocational qualifications and to obtain the certificate of secondary education after two years of studying. The students were recruited from workers who had completed basic vocational schools and distinguished themselves by being socially and professionally active. The goal of the newly-created educational institution was to prepare good specialists for the national economy and active party members. The schools began their didactic work in September 1971. Good conditions of studying were created in them for adult students who were also engaged in the ruling party's activity. The students were able to fully take advantage of the education offered to them for their own individual development, their further vocational education, as well as social advancement.